Colours on East Asian Maps Their Use and Materiality in China, Japan and Korea between the Mid-17th and Early 20th Century - Lange, Diana (Brill, 2023)
With a multi-perspective approach and transdisciplinary methods (humanities and sciences), this book offers an in-depth and systematic study of hand-drawn and hand-coloured maps from East Asia. Map colouring provides an insight into past societies, landscapes and territories. Colour is an important key to a more precise understanding of the map's content, purposes and uses; moreover, colours are also an important aspect of a map's materiality. The material scientific analysis of colourants makes it possible to find out more about maps' material nature and their production as well as the social, geographical and political context in which they were made. 'Reading' colours in this way gives a glimpse into the social lives of mapmakers as well as map users and reveals the complexity of the historical and social context in which maps were produced and how the maps were actually made.